The Complete Paralegal Certification Handbook, 5th Edition - Virginia Koerselman Newman (Cengage Learning, 2020)
Prepare for any of the top three paralegal certification exams with the only comprehensive review resource designed to help new or experienced paralegal professionals earn certification. Koerselman Newman's THE COMPLETE PARALEGAL CERTIFICATION HANDBOOK, 5E equips you to take certification exams from the National Association of Legal Assistants (NALA), National Association of Legal Secretaries and Legal Professionals (NALS), or National Federation of Paralegal Associations (NFPA). The author applies years as an attorney, instructor, and working professional to help you achieve certification goals. New side-by-side comparisons present areas of paralegal practice that are tested with details of eligibility, application and testing requirements, and essential content for each exam. Three new chapters focus on the latest test content, including interviewing, estate planning and probate, and tort law. New examples, outlines, practice tests, and testing tips help refine your skills for certification testing and career success. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.